The Death of Jaromír Czernin 1908 - Michal Jirman (Theatrum Historiae)
This article evaluates the death and funeral culture in the high aristocratic society of the Habsburg monarchy at the turn of the twentieth century, focusing on the illness and death of the mostly forgotten Count Jaromír Czernin (1818–1908). It attempts a comparison with other cases that took place within a similar period and social milieu, and tries to define what constituted an ordinary funeral ceremony. The text below illustrates that this specific funeral was entirely typical in its time within this stratum of societ . The article uses mostly archive sources from the family archive in Jindřichův Hradec and articles from newspapers of the time.